2002
DOI: 10.1097/00000658-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival of Patients Receiving Active Immunotherapy With Canvaxin Therapeutic Polyvalent Vaccine After Complete Resection of Melanoma Metastatic to Regional Lymph Nodes

Abstract: ObjectiveTo determine whether adjuvant postoperative active specific immunotherapy with a therapeutic polyvalent vaccine (PV) called Canvaxin can prolong survival following complete resection of melanoma metastatic to regional nodes (American Joint Committee on Cancer [AJCC] stage III melanoma). Summary Background DataDespite complete lymphadenectomy, 5-year overall survival (OS) for patients with melanoma metastatic to regional lymph nodes is only 20% to 50%, depending on the number of tumor-involved nodes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(68 citation statements)
references
References 48 publications
2
63
1
2
Order By: Relevance
“…Because it is not possible to detect the quantity of specific tumor gangliosides shed into the circulation, we used a sensitive ELISA protocol for antiganglioside IgM; this assay has been validated for screening sera of melanoma patients receiving a cancer vaccine in a Phase III multicenter clinical trial based at the John Wayne Cancer Institute. 47 In our study, this ELISA revealed that serum levels of anti-GD1a IgM antibody were significantly higher in patients with organ-confined CaP than in healthy controls (p 5 0.02), patients with BPH (p < 0.008) or patients with unconfined CaP (p 5 0.002). The uniquely elevated endogenous immune response to GD1a in our study merits further investigation as an immunologic marker of neoplastic transformation of prostate epithelial cells.…”
Section: Endogenous Immune Response To Gangliosidessupporting
confidence: 52%
See 1 more Smart Citation
“…Because it is not possible to detect the quantity of specific tumor gangliosides shed into the circulation, we used a sensitive ELISA protocol for antiganglioside IgM; this assay has been validated for screening sera of melanoma patients receiving a cancer vaccine in a Phase III multicenter clinical trial based at the John Wayne Cancer Institute. 47 In our study, this ELISA revealed that serum levels of anti-GD1a IgM antibody were significantly higher in patients with organ-confined CaP than in healthy controls (p 5 0.02), patients with BPH (p < 0.008) or patients with unconfined CaP (p 5 0.002). The uniquely elevated endogenous immune response to GD1a in our study merits further investigation as an immunologic marker of neoplastic transformation of prostate epithelial cells.…”
Section: Endogenous Immune Response To Gangliosidessupporting
confidence: 52%
“…GD2 is considered to be immunogenic in human cancers 41,44 and considered as a potential target for both passive [44][45][46] and active specific immunotherapies 47 of melanoma. Although we could not observe any significant difference in the anti-GD2 response among our study groups, we did not test the sera against O-acetylated GD2 only.…”
Section: Endogenous Immune Response To Gangliosidesmentioning
confidence: 99%
“…Still, our controls had a similar 5-year survival rate as a comparable group of melanoma patients after RLND reported in recent literature. 33 A randomized clinical trial with DC vaccination in the adjuvant setting is needed to prospectively validate the efficacy of DC-vaccines in the adjuvant treatment following RLND for melanoma. The introduction of adjuvant DC vaccination after RLND would not interfere with the current standard of care, especially in Europe where IFN-a is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between BRAF mutation and Breslow thickness could be suggestive of the unrelatedness of BRAF mutation to genetic instability during early stages of primary tumor growth. Breslow thickness is known as one of the strongest prognostic factors in early stage melanoma (14,19). BRAF mutation acquisition is unlikely attributable to primary tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Proportional hazards test was used to isolate factors influencing the survival. Multivariate analyses considered age, sex, Breslow thickness, presence or absence of lymph node metastasis, site, and presence or absence of BRAF mutation (14). All statistical calculations were performed with SAS software version 3.2.1 (SAS Institute, Cary, NC).…”
Section: Methodsmentioning
confidence: 99%